2009
DOI: 10.1093/jxb/erp271
|View full text |Cite
|
Sign up to set email alerts
|

The ‘trade-off’ between synthesis of primary and secondary compounds in young tomato leaves is altered by nitrate nutrition: experimental evidence and model consistency

Abstract: Plants allocate internal resources to fulfil essential, yet possibly conflicting, demands such as defence or growth, as hypothesized by the 'growth-differentiation balance theory' (GDB). This trade-off was examined in young tomato plants grown for 25 d using the nutrient film technique with seven nitrate concentrations ([NO(3)]). The modification of primary (growth-related: organic acids, carbohydrates) and secondary (defence-related: phenolics) metabolite concentrations in leaves was assessed. Then a simple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 71 publications
5
52
0
3
Order By: Relevance
“…Nutritional treatment design was adapted from Han et al (2014); it was based on previous knowledge acquired on the tomato plant (see Le Bot et al 2009;Larbat et al 2012Larbat et al , 2014 and established from optimal conditions ensuring maximal growth of tomato plants in our lab conditions (see details in Han et al 2014). From DAS 8, a full nutrient solution adjusted to pH 5.5 was supplied daily to plants in a fully crossed design combining two nitrogen levels (optimal nitrogen [ON] vs. insufficient nitrogen [IN]) with two water levels (optimal water [OW] vs. drought [DT]).…”
Section: Plant Nutrition: Nitrogen and Water Inputsmentioning
confidence: 99%
“…Nutritional treatment design was adapted from Han et al (2014); it was based on previous knowledge acquired on the tomato plant (see Le Bot et al 2009;Larbat et al 2012Larbat et al , 2014 and established from optimal conditions ensuring maximal growth of tomato plants in our lab conditions (see details in Han et al 2014). From DAS 8, a full nutrient solution adjusted to pH 5.5 was supplied daily to plants in a fully crossed design combining two nitrogen levels (optimal nitrogen [ON] vs. insufficient nitrogen [IN]) with two water levels (optimal water [OW] vs. drought [DT]).…”
Section: Plant Nutrition: Nitrogen and Water Inputsmentioning
confidence: 99%
“…It was also observed in the same study that increase in N level beyond 11 mM had an antagonistic efect on alkaloid content [28]. Previous studies have indicated that when plants have N deiciency they tend to have increased concentration of C-based secondary metabolites [29,30]. Future studies that identify critical N levels for important medicinal plant species will guaranty both high production of medicinal material and quantity and quality of bioactive medicinal principles.…”
Section: Physiological Efect Of Nitrogen On Medicinal Plantsmentioning
confidence: 79%
“…QualiTree, which can react to pruning, would be a good framework for future tree-aphid studies. Of course, this also calls for future consideration of nitrogen in the model because of its effect on aphid dynamics in trees (Sauge et al 2010) and more generally its implication in the trade-off between defence and growth in plant-pest interactions (Le Bot et al 2009). …”
Section: Discussionmentioning
confidence: 99%